Faktor Keuangan Sebagai Prediktor Manajemen Pajak pada Industri Dasar dan Kimia yang Terdaftar di Bursa Efek Indonesia - Hani Ardiani; Anita Damajanti (Neolectura, 2021)
The basic and chemical industry has the characteristics of being a pioneer industry that has the opportunity to get a reduction in the tax burden. This study will examine whether the company's financial factors, namely assets, profitability, leverage, fixed asset intensity, and inventory intensity can be used as predictors of tax management in basic and chemical industries listed on the Indonesia Stock Exchange. The source of the data for this research is the company's financial statements which are accessed through the idx.co.id website. The observation period is 2016-2019. The criteria for selecting the sample are having been listed on the Indonesia Stock Exchange in the 2016-2019 period, not experiencing losses and using the rupiah currency for financial reporting. The results of data collection obtained 88 (eighty eight) data from 22 (twenty two) companies that meet the sample criteria. Hypothesis testing with multiple linear regression found empirical evidence that profitability, firm size as proxied by total assets, and fixed asset intensity can be used as predictors of tax management variables. Leverage and inventory intensity cannot be used as predictors of tax management by basic and chemical industrial companies.